FINANCIAL LITERACY, ACCESS TO CAPITAL, AND FINANCIAL MANAGEMENT PRACTICES AMONG FISHERMEN ENTREPRENEURS - Abdullah, Fahri; Samsidar, Samsidar (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study investigates the relationship between financial literacy, access to capital, and financial management practices among fishermen entrepreneurs in Indonesia. Despite their vital role in coastal economies, fishermen remain among the most financially vulnerable groups due to low financial knowledge, limited credit access, and weak managerial capacity. Using a quantitative explanatory design, data were collected through structured questionnaires distributed to 120 fishermen entrepreneurs in South Sulawesi and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that financial literacy significantly enhances access to capital and directly improves financial management practices, including budgeting, saving, and expenditure control. Access to capital also has a strong positive effect on financial management and partially mediates the relationship between financial literacy and financial management practices. These findings validate the financial capability framework, emphasizing that financial outcomes are shaped by the interaction between knowledge, institutional access, and behavioral application. The study contributes to the growing literature on financial literacy in developing economies by contextualizing it within the fisheries sector, an area rarely examined in prior research. Policy implications highlight the need for targeted financial education, adaptive microfinance programs, and inclusive financial services tailored to the seasonal income patterns of fishermen. Enhancing financial literacy and inclusion is essential for empowering fishermen entrepreneurs, promoting sustainable livelihoods, and strengthening the resilience of coastal communities